Criterion validity of the PHQ-9 (Malay Version)in a primary care clinic in Malaysia. - Mohd Sidik, Sherina; Arroll, Bruce; Goodyear-Smith, Felicity (Malaysian Medical Association, 2012)
OBJECTIVE: This study was conducted to determine the validity of the 9-item Patient Health Questionnaire (PHQ-9) (Malay version) as a case-finding instrument for depression among women in a primary care clinic. METHODS: A cross sectional study was conducted in a primary care clinic in Malaysia. Consecutive adult women patients who attended the clinic during data collection were given self-administered questionnaires, which included the PHQ-9 (Malay version). Systematic weighted random sampling was used to select participants for Composite International Diagnostic Interviews (CIDI). The PHQ-9 was validated against the CIDI reference standard. RESULTS: The response rate was 87.5% for the questionnaire completion (895/1023), and 96.8% for the CIDI interviews (151/156). The prevalence of depression was 12.1% (based on PHQ-9 scores of 10 and above). The PHQ-9 had a sensitivity of 87% (95% confidence interval 71% to 95%), a specificity of 82% (74% to 88%), positive LR 4.8 (3.2 to 7.2) and negative LR 0.16 (0.06 to 0.40). CONCLUSIONS: The Malay version of the PHQ-9 was found to be a valid and reliable case-finding instrument for depression in this study. Together with its brevity, it is a suitable case-finding instrument to be used in Malaysian primary care clinics.